Ammonia-rich high-temperature superconducting intercalates of iron selenide revealed through time-resolved in situ X-ray and neutron diffraction. - Sedlmaier, S; Cassidy, S; Morris, R; Drakopoulos, M; Reinhard, C; Moorhouse, S; O'Hare, D; Manuel, P; Khalyavin, D; Clarke, S (2014)
The development of a technique for following in situ the reactions of solids with alkali metal/ammonia solutions, using time-resolved X-ray diffraction methods, reveals high-temperature superconducting ammonia-rich intercalates of iron selenide which reversibly absorb and desorb ammonia around ambient temperatures.